Nonperturbative approach to potentials in impenetrable boxes based on quasi-exact solvability - Dutra, Alvaro de Souza [UNESP] (Iop Publishing Ltd, 2003)
In this work we develop an approach to obtain analytical expressions for potentials in an impenetrable box. In this kind of system the expression has the advantage of being valid for arbitrary values of the box length, and respect the correct quantum limits. The similarity of this kind of problem with the quasi exactly solvable potentials is explored in order to accomplish our goals. Problems related to the break of symmetries and simultaneous eigenfunctions of commuting operators are discussed.